Preferensi Konsumen terhadap Kedai Kopi di Kota Denpasar - DIMAS ALI SETYO BUDI; I MADE SUDARMA; I DEWA GEDE AGUNG (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Consumers Preference for Coffee Shop in the City of Denpasar Consumers preference is the tendency of consumers to consume certain goods or services and the satisfaction gained from that consumption results in loyalty to certain products even though there are many various similar products. Consumers are influenced by conditions and information about service, facilities, location, price, promotion and taste. The purpose of this research is to identify the characteristic of coffee shops consumers and analyze their preference. The research was conducted in four coffee shops in the city of Denpasar. The study uses accidental sampling method and involved 100 respondents from an unknown number of population. Based on descriptive analysis, the characteristics of coffee shop consumers in Denpasar are found: consumers are dominated by males; consumers age range between 27-32 year old; consumers educational backgrounds are mostly undergraduate; the occupation of the consumers are mostly student; and the intensity of visiting the coffee shops is at least 4 times a month. Based on the analysis using SEM-PLS, it could be concluded that service, facilities, location, price, promotion and taste have positive and significant influence on consumers preference for coffee shop in the city of Denpasar. Coffee shop owners and managers need to improve services and facilities in order to improve convenience for consumers. In terms of location and promotion, coffee shop owners must choose the best location to maximize direct promotions. The correlation between price and taste offered has to be maintained. Price could also be increased through improved facilities and services.